(untitled) (UNED Research Journal, 2022)
Introduction: Disability has been considered as a difficulty in carrying out activities necessary for life. Objective: To identify factors associated with disability in basic and instrumental activities of daily living in people aged 60 and over residing in Costa Rica. Methods: The study included 2238 people participating in the Costa Rica project: Longevity and Healthy Aging Study. Logistic regression models were estimated and odds ratios were calculated in order to identify factors associated with disability. Results: Factors that influence disability in combined activities are the presence of pain, the lack of physical activity and C-reactive protein. The factors with the greatest impact on basic activities were the presence of pain, the lack of physical activity and the presence of chronic disease. For instrumental activities, negative self-rated health and pain had the greatest impact, after physical activity. In addition, conditions such as diabetes affect activities of daily living. Conclusion: Pain, not performing physical activity, self-rated health and other sociodemographic factors cause functional difficulties that affect the quality of life of people aged 60 and over.